Behavioral variant of frontotemporal dementia or frontal variant of Alzheimer's disease? A case study - Leonardo Cruz de Souza; Luciano Inácio Mariano; Renata Freire de Moraes; Paulo Caramelli (Dementia & Neuropsychologia, 2019)
ABSTRACT Alzheimer's disease (AD) has heterogeneous clinical presentations. Amnestic progressive disorder leading to dementia is the most typical, but non-amnestic presentations are also recognized. Here we report a case of frontal variant of AD. A right-handed woman, aged 68 years, was referred for progressive behavioral disorders and personality changes. She had a corroborated history of dietary changes, hyperorality, impulsivity, affective indifference and apathy, with functional impairment. Cognitive assessment yielded severe executive deficits. Positron emission tomography with fluorodeoxyglucose showed marked hypometabolism in frontotemporal regions, with relative preservation of parietal regions. CSF AD biomarkers showed low Aβ42, high Tau and high P-Tau. The patient fulfilled criteria for probable behavioral variant frontotemporal dementia. However, considering the AD pathophysiological signature on CSF biomarkers, a diagnosis of frontal variant of AD was established. In the perspective of disease-modifying therapies, it is important to identify atypical Alzheimer presentations, as these patients may be candidates for specific treatments.